Resin-bonded fixed partial denture as a cost-effective prosthesis for missing maxillary lateral incisor in a cleft lip and palate patient: a case report - Rayavarapu, Sunil; Sajjan MC, Suresh; Mantena , Satyanarayana Raju; Bheemalingeswara Rao, D; Anil, Budumuru; Prem Sagar, Yekula (International Journal of Dental Materials, 2022)
Literature suggests 66.7% of dental abnormalities among patients with cleft lip and palate (CLP). Besides posing functional difficulties, dental anomalies also raise significant aesthetic concerns among these patients, especially with missing teeth in the anterior region. Among various treatment choices like a removable partial denture, fixed and implant treatments available in the prosthetic rehabilitation of missing teeth in CLP subjects, Maryland bridges offer a conservative and cost-effective alternative in short-span edentulous spaces while carrying the advantages of supragingival marginal preparations and less intensive working times. The availability of advanced self-etch adhesive systems that chemically bond to both the tooth and metal surfaces offer these prostheses more longevity. This case report presents the fabrication of a resin-bonded fixed partial denture in the prosthetic rehabilitation of a missing maxillary lateral incisor in a 23-year-old female patient with CLP who was unwilling for orthodontic care.